Surviving Hitler and Mussolini : daily life in occupied Europe - Gildea, Robert; Wieviorka, Olivier, 1960-; Warring, Anette, 1958- (Occupation in Europe series., 2006)
Examining how far everyday life was possible in a situation of total war and brutal occupation, this book's theme is the social experience of occupation in German- and Italian-occupied Europe, and in particular the strategies ordinary people developed in order to survive. It adopts a comparative approach, and also discusses the Second World War.